Tierra, trabajo y reciprocidad - Ramirez, Delia Concepción (2023)
This article is a systematization of the experience of an emblematic organization for family farmers in the Alto Paraná region of Misiones: Independent Producers of Piray (PIP), in the Union of Land Workers (UTT). The analysis has been carried out considering two articulated dimensions a) the collective organizational actions linked to the conditions of possibility, which in turn are permeated by conjunctural influences, and b) the trajectories and biographies of individual actors that account for the local history of the territory. This articulation has made it possible to analyze the political practices imbricated in the strategies of social reproduction. This systematization arises from the need to reconstruct a local history based on reflections within the framework of ethnographic involvement. The main contribution of the text lies in the identification of the reciprocities established around neighborhood and kinship, without which the political action of organized producers and the subsistence of the local population could not be understood.